Pengaruh Konten Parenting dari Influencer Sosial Media Instagram terhadap Gaya Pengasuhan Orang Tua Generasi Milenial - Maulida, Luluk Rochaina; Sumanto, Reni Pawestuti Ambari (Riwayat: Educational Journal of History and Humanities, 2025)
Social media has become a part of human life and also parents. One of the popular platforms among millennial parents is Instagram. The existence of social media platforms has led to the term Instagram influencers who present various content, for example, the parenting practices they use. This study aims to analyze the influence between parenting content from Instagram influencers on the parenting style of millennial generation parents. The quantitative method was chosen to determine the amount of influence between these two variables. Quota sampling was used in determining the research sample with predetermined criteria. The data collection technique used a questionnaire filled out by 100 respondents. The data analysis techniques used in this study are t hypothesis test, coefficient of determination and simple linear regression analysis. The results of the study based on the t hypothesis test, the coefficient of determination, and simple linear regression analysis provide the results that the parenting content variable of Instagram social media influencers (X) has a significant effect on the parenting style of millennial generation parents (Y).